2022
DOI: 10.3389/fphy.2022.862962
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals and Applications of Topological Polarization Singularities

Abstract: Radiations towards the continuum not only brings non-Hermicity to photonic systems but also provides observable channels for understanding their intrinsic physics underneath. In this article, we review the fundamental physics and applications of topological polarization singularities, which are defined upon the far-field radiation of photonic systems and characterized by topological charges as the winding numbers of polarization orientation around a given center. A brief summarizing of topological charge theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 177 publications
0
7
0
Order By: Relevance
“…For planar photonic structures, distributed Bragg reflectors (DBRs) are often used as a cavity in the vertical dimension [140144] . However, nowadays, the BIC can enhance the strong photon-exciton coupling instead of DBR mirrors because BIC cavities provide higher Q factor and near-infinite photon lifetime [16,22,145] . Therefore photonic CQED systems can more easily achieve strong coupling and obtain large Rabi splitting, leading to strong implications for polaritons in quantum information processing [146,147] .…”
Section: Explored Effects Enabled By Bicsmentioning
confidence: 99%
“…For planar photonic structures, distributed Bragg reflectors (DBRs) are often used as a cavity in the vertical dimension [140144] . However, nowadays, the BIC can enhance the strong photon-exciton coupling instead of DBR mirrors because BIC cavities provide higher Q factor and near-infinite photon lifetime [16,22,145] . Therefore photonic CQED systems can more easily achieve strong coupling and obtain large Rabi splitting, leading to strong implications for polaritons in quantum information processing [146,147] .…”
Section: Explored Effects Enabled By Bicsmentioning
confidence: 99%
“…It is found that a class of unidirectional guided resonances (UGRs) (54,(57)(58)(59) can be realized by merging a pair of half-integer topological charges upon one side of the grating while leaving them apart on the other side (54,57), resulting in the radiation only toward a single side without putting a mirror on the other side. The UGRs are proved to be ubiquitous in periodic photonic structures (including the geometries already adopted in many grating couplers), because the desired half-charges can be either created from splitting an integer charge carried by a bound state in the continuum (BIC), namely, discrete, infinite lifetime states embedded in the radiation continuum (60)(61)(62)(63)(64)(65)(66)(67); or alternatively, spawned from a void point owing to the interband coupling effect (54,57). Nevertheless, how to use the UGRs to construct a complete, practical, and fabricationfriendly grating coupler for substantially lowering the loss of optical interconnects remains an important but elusive problem.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] The sum of the quantized topological indices, termed Hopf indices or topological charges (TCs), is an invariant. [ 2–7 ] The TC can be decomposed by fragmentation in the momentum space in more elementary singularities of half‐integer indices ±1/2 associated to circularly polarized singularities known as C‐points, that is, pure circular polarization states with undetermined major axis. As instance, a V‐point, that is, a state with undetermined linear polarization, is the intersection of two C‐lines running in opposite directions with opposite circular polarization.…”
Section: Introductionmentioning
confidence: 99%